Exploring Emotional Intelligence in Semester 3 Cadets at Maritime Institute Jakarta: Implications for Maritime Management and Education - Marudut Bernadtua Simanjuntak (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research delves into the intricate dynamics of emotional intelligence among Semester 3 cadets at the esteemed Maritime Institute Jakarta (STIP Jakarta). As the maritime industry places increasing emphasis on holistic competence, this study investigates the intersection of emotional intelligence, academic self-assessment, professional competences, and motivations. Over a span of three semesters, approximately 18 months, 240 cadets were engaged in a qualitative exploration, providing insights into their perspectives on emotional intelligence within the unique context of maritime education. The findings reveal a compelling correlation between emotional intelligence and academic self-checks, indicating that cadets with higher emotional intelligence levels exhibit proactive approaches to academic responsibilities. Moreover, emotional intelligence emerges as a significant influencer of professional competences, with high levels associated with effective decision-making and adaptive leadership. Intrinsic motivations play a pivotal role in shaping emotional intelligence, aligning cadets' passion with career aspirations and fostering genuine dedication to the maritime industry. The implications of this research are far-reaching. The recognition of emotional intelligence as a critical factor in academic success suggests the need for tailored interventions within the maritime education curriculum. Integrating modules focused on emotional intelligence development can equip cadets with essential skills for academic resilience and effective professional navigation. Furthermore, the study recommends mentorship programs, intrinsic motivation enhancement strategies, and collaborative initiatives between educational institutions and industry stakeholders to foster a workforce adept at emotional intelligence and ready for the challenges of maritime management. While the research contributes valuable insights to the discourse on emotional intelligence in maritime education, it also highlights the need for continued exploration. Future research could broaden the scope to include diverse cadet populations and employ additional research methods to validate and extend the current findings. This study stands as a foundational step towards understanding and enhancing emotional intelligence among maritime professionals, positioning them as not only technically proficient but also resilient and adaptive leaders in the global maritime arena.